Persepsi Diri dan Hubungan Teman Sebaya: Studi Korelasional di SMK Negeri 4 Kalabahi - Wahon, Angela Alisia; Pua Upa, M. D.; Indrawan, Putu Agus (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
This study investigates the relationship between self-perception and peer association among vocational high school students at SMK Negeri 4 Kalabahi. Using a quantitative correlational research design, data were collected from 63 students selected through proportional stratified random sampling. Two Likert-scale questionnaires, measuring self-perception and peer association, were validated for content and reliability, achieving Cronbach’s alpha values of 0.820 and 0.899, respectively. Descriptive statistics revealed that 74.6% of participants exhibited high self-perception, and 65.1% reported high peer association. Normality and linearity assumptions were met, and Pearson’s product-moment correlation indicated a low but statistically significant positive relationship between self-perception and peer association (r = 0.275, p < 0.05). The findings suggest that students with higher self-perception are more likely to engage positively with peers, although the strength of the association is modest. These results highlight the multifactorial nature of adolescent social development, where self-perception interacts with environmental, social, and personal variables. The study emphasizes the need for educational interventions that foster positive self-perceptions and supportive peer environments, contributing to improved adolescent well-being and academic engagement.